2012
DOI: 10.1080/14693062.2011.637819
|View full text |Cite
|
Sign up to set email alerts
|

Initial public reactions to carbon capture and storage (CCS): differentiating general and local views

Abstract: Carbon capture and storage (CCS) is considered a potential climate change mitigation option, but public opposition may hamper its implementation. A quasi-experimental approach is used to examine whether 'not in my back yard' (NIMBY) sentiments can be anticipated at the initial stage when CO 2 storage locations have been selected and communicated to the public. Furthermore, the psychological structure of initial reactions to CO 2 storage plans is studied to ascertain the differences between people living in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…NIMBY reactions (general support for CCS adoption but opposition to local projects) have been explained by individual values, namely the perception of the effects of CCS in society at large [14]. Trust in government has been shown to be a key factor in the inclination to protest, interacting with risk perception [13]. There are, then, estimates of some of the effects on non-CCS related values, opinions and beliefs on reactions to CCS.…”
Section: Ccs In Societymentioning
confidence: 98%
See 1 more Smart Citation
“…NIMBY reactions (general support for CCS adoption but opposition to local projects) have been explained by individual values, namely the perception of the effects of CCS in society at large [14]. Trust in government has been shown to be a key factor in the inclination to protest, interacting with risk perception [13]. There are, then, estimates of some of the effects on non-CCS related values, opinions and beliefs on reactions to CCS.…”
Section: Ccs In Societymentioning
confidence: 98%
“…Here, the reactions of local publics to storage projects have been under great scrutiny [11,12]. Not-in-my-backyard (NIMBY), or more accurately, not-under-my-backyard, effects have been differentiated from general reactions by measuring the reactions of offsite and onsite publics [13]. NIMBY reactions (general support for CCS adoption but opposition to local projects) have been explained by individual values, namely the perception of the effects of CCS in society at large [14].…”
Section: Ccs In Societymentioning
confidence: 99%
“…Trust in government, its institutions and regulatory framework (Terwel and Daamen 2012) is a particularly important factor in discussions about herbicide use. Due to the negative colonial legacy, there is a host of historical and current reasons why First Nations mistrust non-Aboriginal society, especially its governments and their agencies (Adams 1989, Cardinal 1999.…”
Section: Mistrust Of the Regulatory Frameworkmentioning
confidence: 99%
“…Studies indicate that views on CCS vary across countries according to national energy issues, that the public prefers renewable energy sources to CCS, and that the public has limited expectations with regard to the future importance of CCS (Fleishman et al 2010;Kraeusel and Möst 2012;Oltra et al 2010;Pietzner et al 2011;Shackley and McLachlan 2006;Upham and Roberts 2011). In terms of local considerations, studies have found that compensation to local communities, risk and safety of people, and perceived community benefits are important to public perceptions (Bradbury et al 2009;Brunsting et al 2011;Terwel and Daamen 2012). 1 In addition, a survey of U.S. households was appropriate because the worldview measurement instrument was constructed for U.S. social, cultural and political conditions (Kahan et al, 2011). Wind energy is a more mature technology than CCS.…”
mentioning
confidence: 99%
“…The effect of communication on public perceptions depends on early engagement and the level of confidence in the source of information, with industry and government inspiring less confidence and researcher and NGOs inspiring more confidence (Bradbury et al 2009;Brunsting et al 2011;Terwel and Daamen 2012;Upham and Roberts 2011). Studies indicate that views on CCS vary across countries according to national energy issues, that the public prefers renewable energy sources to CCS, and that the public has limited expectations with regard to the future importance of CCS (Fleishman et al 2010;Kraeusel and Möst 2012;Oltra et al 2010;Pietzner et al 2011;Shackley and McLachlan 2006;Upham and Roberts 2011).…”
mentioning
confidence: 99%